German Nationalism and Religious Conflict : Culture, Ideology, Politics, 1870-1914 - Smith, Helmut Walser (Book collections on Project MUSE., 2014)
The German Empire of 1871, although unified politically, remained deeply divided along religious lines. In German Nationalism and Religious Conflict, Helmut Walser Smith offers the first social, cultural, and political history of this division. He argues that Protestants and Catholics lived in different worlds, separated by an ""invisible boundary"" of culture, defined as a community of meaning. As these worlds came into contact, they also came into conflict. Smith explores the local as well as the national dimensions of this conflict, illuminating for the first time the histor.